Robust colonoscope tracking method for colon deformations utilizing coarse-to-fine correspondence findings - Oda, Masahiro; Kondo, Hiroaki; Kitasaka, Takayuki; Furukawa, Kazuhiro; Miyahara, Ryoji; Hirooka, Yoshiki; Goto, Hidemi; Navab, Nassir; Mori, Kensaku (International Journal of Computer Assisted Radiology and Surgery, 2017)
Purpose: Polyps found during CT colonography can be removed by colonoscopic polypectomy. A colonoscope navigation system that navigates a physician to polyp positions while performing the colonoscopic polypectomy is required. Colonoscope tracking methods are essential for implementing colonoscope navigation systems. Previous colonoscope tracking methods have failed when the colon deforms during colonoscope insertions. This paper proposes a colonoscope tracking method that is robust against colon deformations. Method: The proposed method generates a colon centerline from a CT volume and a curved line representing the colonoscope shape (colonoscope line) by using electromagnetic sensors. We find correspondences between points on a deformed colon centerline and colonoscope line by a landmark-based coarse correspondence finding and a length-based fine correspondence finding processes. Even if the coarse correspondence finding process fails to find some correspondences, which occurs with colon deformations, the fine correspondence finding process is able to find correct correspondences by using previously recorded line lengths. Result: Experimental results using a colon phantom showed that the proposed method finds the colonoscope tip position with tracking errors smaller than 50 mm in most trials. A physician who specializes in gastroenterology commented that tracking errors smaller than 50 mm are acceptable. This is because polyps are observable from the colonoscope camera when positions of the colonoscope tip and polyps are closer than 50 mm. Conclusions: We developed a colonoscope tracking method that is robust against deformations of the colon. Because the process was designed to consider colon deformations, the proposed method can track the colonoscope tip position even if the colon deforms.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Colon; Colonoscope tracking; CT image; EM sensor